Adsorption of di-chain cationic and non-ionic surfactant mixtures at the air/water interface - Penfold, J; Staples, E; Tucker, I; Soubiran, L; Creeth, A; Hubbard, J (2000)
We report a preliminary study of the competitive adsorption of the di-chain cationic surfactant distearyloyloxydimethylammonium chloride (DISDAC) and the non-ionic surfactant hexaethylene monododecyl ether (C12E6) at the air/water interface. We used specular neutron reflection, in combination with H-D isotopic substitution, to follow the concentration, composition and temperature dependence of the adsorption of the di-chain cationic-non-ionic surfactant mixture at the air/water interface. The concentration dependence of the surface composition is different above and below the L(α)-L(β)transition temperature of DISDAC. Time dependent effects are observed in the surface absorption and composition, which is associated with the small critical micellar concentration and monomer concentration of DISDAC. The data reported here are the equilibrium values. Hysteresis effects in the surface composition are observed in temperature cycling above and below the L(α)-L(β) transition temperature of DISDAC.